Civil Legal Assistance for Vulnerable Communities: Protecting Civil Rights in the Community - Flora, Henny Saida; Hartawati, A.; Akhyar, Cut Fadhlan; Abrori, Abrori; Dewi, Putri Maha (Civiliza Publishing, 2025)
This article examines the critical role of civil legal assistance in protecting the rights of vulnerable populations, including women, children, indigenous peoples, and persons with disabilities. Despite existing legal frameworks and recent advancements in legal aid provision, significant barriers persist that hinder access to justice for these groups. Through a qualitative analysis of recent literature and case studies from various regions, this study highlights successful models of community-based legal aid initiatives and the impact of non-governmental organizations in promoting social justice. The findings underscore the importance of increasing funding, raising public awareness, and utilizing technology to enhance access to legal resources. By addressing these challenges and implementing effective strategies, societies can ensure that all individuals, regardless of their background or circumstances, have the opportunity to assert their rights and seek justice. This article aims to contribute to ongoing discussions about equitable access to legal services and the necessity of empowering marginalized communities within the broader framework of human rights.